Heterodimetallic Structures Based on Cyano-Substituted Bis(dithiolene) Complexes and Ni and Cu Cyclam Cations - Cerdeira, Ana C.; Belo, Dulce; Rabaça, Sandra; Pereira, Laura C. J.; Coutinho, Joana T.; Simão, Dulce; Henriques, Rui T.; Jeannin, Olivier; Fourmigué, Marc; Almeida, Manuel (European journal of inorganic chemistry, 2013)
Five charge‐transfer salts based on the combination of anionic FeIII and CuII bis(dithiolene) complexes containing nitrile groups with [M(cyclam)]2+ (M = Ni, Cu) cations, namely, [Ni(cyclam)]2[Cu(dcbdt)2]2·4DMF (1, dcbdt = 4,5‐dicyanobenzene‐1,2‐dithiolate, DMF = N,N‐dimethylformamide), [Ni(cyclam)]2[Cu(dcdmp)2]2·4DMF (2, dcdmp = 2,3‐dicyano‐5,6‐dimercaptopyrazine), [Cu(cyclam)]2[Cu(dcdmp)2]2·4DMF (3), [Cu(cyclam)]2[Fe2(cbdt)4]2·4DMF (4, cbdt = 4‐cyanobenzene‐1,2‐dithiolate) and [Ni(cyclam)]2[Fe2(cbdt)4]2·4DMF (5), were prepared and characterised by X‐ray diffraction and magnetisation measurements. The crystal structures of 1–4 were determined by single‐crystal X‐ray diffraction, which revealed that the cyano groups from dithiolene complexes fail to coordinate the metal ions in the cyclam units. Instead, they are coordinated by solvent molecules or by dithiolene S atoms and cyclam N–H groups, which participate in hydrogen bonds to the nitrile and sulfur moieties in the anions. Heterodimetallic structures based on the combination of anionic FeIII and CuII bis(dithiolene) complexes containing nitrile groups with [M(cyclam)]2+ (M = Ni, Cu) cations display a new coordination mode of the dithiolene S atom towards the metal cyclam.